Andrographis paniculata (Kalmegh): A Review - Mishra, Siddhartha K.; Sangwan, Neelam S.; Sangwan, Rajender S. (Pharmacognosy Reviews)
Andrographis paniculata (Burm.f.) Nees (Acanthaceae) is a medicinal plant traditionally used for the treatment of cold, fever, laryngitis and several infectious diseases ranging from malaria to dysentery and diarrhea in China, India and other south east Asian countries. The plant is claimed to possess immunological, antibacterial, antiinflammatory, antithrombotic and hepatoprotective properties. In Malaysia, the plant is used in folk medicines to treat diabetes and hypertension. The contents of diterpenoids like andrographolide, neoandrographolide and dehydroandrographolide are the chief criteria for monitoring the quality of A. paniculata. Andrographolide, though found in all plant parts, is most concentrated in the leaves. It is a diterpene containing a γlactone ring connected to a decalin ring system via an unsaturated C-2 moiety. It has multiple pharmacological properties such as protozoacidal, antihepatotoxic, anti-HIV, anticancer, antitumor, hypoglycemic and hypotensive activities. Andrographolide is an interesting pharmacophore with anticancer and immunomodulatory activities and hence has the potential to be developed as an anticancer chemotherapeutic agent as well. In this review, we have explored the various dimensions of the Andrographis paniculata plant and compiled its vast pharmacological applications to comprehend and synthesize the subject of its potential image of multipurpose medicinal agent. The plant is widely cultivated to large regions of the world and its importance as a medicinal plant is growing up substantially with increasing and stronger reports in support of its multifarious therapeutic uses.
Keywords: Andrographis paniculata; andrographolide; neoandrographolide; hepatoprotective; anticancer; antitumor; antiHIV; medicinal plant